Fenomena Azan Pertama Jumat Lima Muazin: Kajian Living Hadis di Masjid Sholihin - Aufa Yuvela Rafif (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2023)
The Friday prayer call (adhan) varies across mosques in Indonesia. A unique tradition is found at Sholihin Mosque, located on Jalan Kaliurang Km 9.3, Tambakan, Sinduharjo, Ngaglik, Sleman, where five muezzins simultaneously recite the first adhan. Although this practice has been maintained for years, its normative basis and deeper meaning remain largely unexplored by the local community. This qualitative study employs historical documentation as the primary data collection method, supplemented by interviews and observations, emphasizing interviews involving relevant figures such as the muezzins, mosque administrators (takmir), and congregants. The data are analyzed using a descriptive-interpretative approach, in which the information is organized, interpreted, and concluded using Max Weber’s theory of social action. In addition, relevant hadith texts from the nine canonical collections (Kutub al-Tis’ah) and other supporting Islamic literature are used to enrich the analysis. The findings reveal that the first adhan performed by five muezzins is understood by the community as a cultural and religious identity unique to Sholihin Mosque, valued for its historical background, religious grounding, and distinctiveness. Furthermore, this tradition is viewed by the muezzins as a form of worship believed to bring spiritual reward in the hereafter. These perspectives motivate the community’s commitment to preserving the practice as a meaningful expression of local religious life within the broader context of living hadith.